Análise da competitividade da produção de compensado de Paricá no Estado do Pará - Santos, Iêdo Souza (Universidade Federal de São Carlos, 2017)
In recent years, the Pará state plywood industry, which had the most important in the country, has been undergone large changes. The main raw material of the activity, that is, the wood, has been no more obtained by means of the exploitation of native forest, but has been gradually replaced by planted forest of paricá, a region native species. In addition to possess the desirable technological characteristics for plywood production, the paricá has fast growth and high yield, which contribute to its use as an input into the analyzed productive chain. In order to better understand that scenario, this paper aimed analyzing the production chain paricá plywood in the state of Pará as a way of proposing policies that could increase its competitiveness in a sustainable manner. Therefore, a theoretical model based on competitiveness drivers was applied, after its adequate adjust to specificities of the investigated area. The following drivers were examined: institutional environment; market structure; governance structure; input and infrastructure; management; technology and environmental sustainability. About the links of the chain, these were: the production of paricá and its transformation into plywood. In the first, that is, in the wood production, the governance structure driver was the one that received better assessments, whereas the technology proved to be the main bottleneck. In the industrialization of plywood by its turn, three drivers presented positive assessment, with emphasis on the availability of inputs at the concerned locale. By other side, the management of factory unit configured as an obstacle to the activity, and was considered inadequate for, usual patterns. In general, the governance structure was the only driver that presented good assessments for both analyzed links, while institutional environment, management and technology constituted in the main sources of inefficiency. Therefore, these three drivers are the main bottlenecks against improving the competitiveness of the paricá plywood production chain in Para. Among the improvements that could be implemented in, public policies, stood out: debureaucratization of access to credit; creation of the State Fund for Forests to encourage research and investments. Among private policies, it was suggested that industries organize themselves by representations and invest in the people qualification and the reform of the technological park.
Analysis of competitiveness of Paricá plywood production in the State of Pará
Keywords: Modelo; Direcionadores da competitividade; Painel de madeira; Microrregião de Paragominas; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA